Rancang Alat Heater untuk Pembuatan N-Butanol Menggunakan Proses Hidrogenasi - Frengki Boy Hutasoit; Kun Aussieanita Mediaswanti (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2021)
n-Butanol is one of the intermediate materials used as raw material for downstream industries such as the textile, polymer, plastic, paint, surface coating, pharmaceutical, and others industries. There are several methods that can be used in the manufacture of n-Butanol, one of which is the hydrogenation process, where the raw material butyl butyrate is reacted with hydrogen gas in a Fixed Bed Multitube Reactor using a solid catalyst to produce n-Butanol. The n-Butanol plant is designed with a capacity of 5,000 tons/year. The factory operates 330 days a year, with a production process of 24 hours/day. The reaction occurs in the gas phase with a temperature of 280°C and a pressure of 10 atm, the reaction is exothermic using a Cu/ZnO/Al2O3 catalyst with a mole ratio of reactant butyl butyrate and hydrogen of 1:14 and produces a product conversion of n-Butanol of 90%. Further purification was carried out using a distillation tower in the form of n-Butanol with a purity of 99.50%. The device is designed in the form of a heater that functions as a hydrogen heater from a temperature of 30°C to 280°C before being sent to the reactor. The heating medium used is steam from the boiler. Hydrogen flowing in the heater with a capacity of 119.44 kg/hour and after calculations, obtained a heater of the double pipe heat exchanger (DPHE) type, pipe dimensions 21/2 inch x 11/4 inch with 3 hairpins, pipe length 20 ft. the annulus flows hydrogen and the pipe flows steam as a heater. The heater uses a construction material in the form of carbon steel.